Structural Modeling of Higher Education Based on Sustainable Development Components Using a Mixed Method (Case Study: South Pars Region) - Jahanbakhsh , Mansour; Hosseinpour , Abdul Karim; Hadi Peikani, Mehraban (Management Strategies and Engineering Sciences, 2024)
The aim of this study is to structurally model higher education based on sustainable development components using a mixed-method approach. This applied research employs a mixed-method (qualitative-quantitative) design. The statistical population includes 12 specialists and academic experts in the field of sustainable development in general, and sustainable development in higher education in particular. In the qualitative section, their opinions were used to identify and code the categories. For the modeling process, the statistical population consisted of faculty members, postgraduate students from the Persian Gulf University, and specialists from the South Pars Special Economic Zone, including experts in environmental sciences, economics, social sciences, and faculty members and postgraduate students from Persian Gulf University. The sample size was calculated using Cochran’s formula for unknown populations, resulting in a sample size of 384 individuals, with a random accessible sampling method. To identify the factors, interviews were conducted, and through open, selective, and axial coding, categories and concepts were extracted. The results of this phase yielded 451 open codes, 24 axial codes, and 8 selective codes. Subsequently, in the next phase, the Delphi technique was used to filter the central, causal, contextual, intervening, strategic, and outcome conditions through three rounds of screening. Ultimately, consensus was reached on 135 open codes. For the modeling process, structural equation modeling and partial least squares (PLS) software were used. The results of the study revealed that the structural modeling of higher education based on sustainable development components, using the mixed method, includes 2 causal conditions and 8 subcriteria, 1 contextual condition and 3 subcriteria, 1 intervening factor and 2 subcriteria, 2 strategies and 5 subcriteria, and finally, 2 major outcomes with 5 subcriteria. These outcomes, ranked by priority, are the development of sustainable projects and businesses (with a factor loading of 0.633) and the management of natural resources and the environment (with a factor loading of 0.524). Consequently, it can be concluded that focusing on sustainable development in the region enhances business development and the conservation and management of natural resources.